2019
DOI: 10.1038/s41366-019-0381-5
|View full text |Cite
|
Sign up to set email alerts
|

Do physical activity, commuting mode, cardiorespiratory fitness and sedentary behaviours modify the genetic predisposition to higher BMI? Findings from a UK Biobank study

Abstract: Objective-Investigate associations between a genetic profile risk score for obesity (GPRS-obesity) (based on 93 SNPs) and body mass index (BMI) was modified by physical activity (PA), cardiorespiratory fitness, commuting mode, walking pace and sedentary behaviours. Methods-For the analyses we used cross-sectional baseline data from 310,652 participants in the UK Biobank study. We investigated interaction effects of GPRS-obesity with objectively-measured and self-reported PA, cardiorespiratory fitness, commutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
10
0
1
Order By: Relevance
“…Recently, the Sedentary Behavior Research Network (SBRN; a network connecting sedentary behavior researchers and health professionals from around the world) updated its definitions on, among others, sedentary behavior and physical inactivity and thereby supported that an insufficient physical activity level is not the same as sedentary behavior 1 . This idea is supported by the modest inverse correlations detected between objective sedentary time and MVPA in this study, matching those observed in earlier studies 16‐18 . This confirms that sedentary time is not simply the inverse of MVPA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, the Sedentary Behavior Research Network (SBRN; a network connecting sedentary behavior researchers and health professionals from around the world) updated its definitions on, among others, sedentary behavior and physical inactivity and thereby supported that an insufficient physical activity level is not the same as sedentary behavior 1 . This idea is supported by the modest inverse correlations detected between objective sedentary time and MVPA in this study, matching those observed in earlier studies 16‐18 . This confirms that sedentary time is not simply the inverse of MVPA.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, there is ongoing debate on whether the risks of sedentary behavior may not simply converge with the risks of not meeting physical activity recommendations (referred to as physical inactivity), as both sedentary behavior and physical inactivity contribute to the burden of chronic diseases 8 . The current literature seems to argue against this idea because there is only a modest relationship between MVPA and sedentary behavior 16‐18 . However, lower levels of MVPA, like higher levels of sedentary behavior, have shown to increase the risk of cardiovascular disease, type 2 diabetes, and certain types of cancer 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches also use simple linear regression, but establish the HR-to-WR relationship by relating resting HR to only a single measurement of HR during the test 20,43,44,22,18,21,45,46,17 . HR measurement noise will greatly decrease precision in this approach, and the CRF estimates are still subject to bias, the extent of which may differ by protocol.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de esto, es importante destacar que los mencionados no son los únicos actores de este ambiente, ya que el consumo excesivo de calorías -independiente del alimento que provengan-tendrá un efecto similar sobre nuestros genes. Cabe destacar el rol de la inactividad fisca, el tiempo que destinamos a estar sentados y otros factores de riesgo emergentes como lo es el tiempo que destinamos a dormir, los cuales también son actores fundamentales de este ambiente de riesgo obesogénico 3,5,6 . Por consiguiente, la promoción e implementación de políticas públicas que permitan reducir estos factores de riesgo son esenciales para ganar la batalla contra la obesidad,…”
Section: Sr Editorunclassified